Microneedling versus fractional CO2 laser in the treatment of atrophic postburn scars - Amira A Zayed; Heba M Mashaly; Heba M Abdel Raheem; Eman El-Nabarawy; Marwa S El-Hawary; Olfat G Shaker; Reham S Elnemer; Waleed E Aldhahebi (Wolters Kluwer Medknow Publications, 2019)
Background Microneedling is an evolving approach in the treatment of postburn scars based on the principle of collagen induction and neovascularization. Objective To evaluate and compare the clinical and histopathological outcome of microneedling versus ablative fractional CO2 laser targeting atrophic postburn scars. Patients and methods Twenty-five patients with atrophic postburn scars were included in this study. Each patient received four treatment sessions of both microneedling and fractional CO2 laser with 4-week interval. Histopathological and histochemical evaluations of collagen and elastic fibers were done. Quantitative morphometric studies were also performed. Results A significant increase in collagen deposition was detected after fractional CO2 laser therapy. A significant increase in elastic fiber deposition was detected after both laser therapy and microneedling with fractional CO2 laser showing more significant results than microneedling. Conclusion Ablative fractional CO2 laser is more effective than microneedling in the treatment of atrophic postburn scars; however, microneedling did show a significant increase in elastic fiber deposition and thus can be a promising therapeutic approach when combined with other treatment modalities.